Resistivitas Batuan Berdasarkan Metode Geolistrik Konfigurasi Schlumberger untuk Menentukan Potensi Air Tanah Sebagai Acuan Sumur Bor - Fadilah Fadilah (SPEJ (Science and Physic Education Journal), 2020)
The purpose of this study is to analyze rock resistivity based on the geoelectric method of the Schlumberger configuration to determine the potential for groundwater as a reference for boreholes. The method used in this research is the geoelectric resistivity method with a Schlumberger configuration. Data acquisition modeling was analyzed using Progress Version 3.0 to describe the subsurface based on measurement sounding points in the field. The main targets for these measurements are confined aquifer traps and sandstone stratigraphy. Field measurement points are at coordinates S 030 43 '52.2 "and E 1020 19' 27.1". The results of this study indicate that the layer that is thought to be the groundwater carrier layer is found at a depth of about 64.99 meters to 150.86 meters with a layer thickness of 85.87 meters, which is in the form of sandstone density with a resistivity value of 5.39 ohm meters. The iteration error scale value in this study is, 5.05% RMS. In conclusion, the results obtained can provide specific information for groundwater drilling actors in the research location. Keywords: Groundwater, Geoelectricity, Resistivity, Schlumberger